45.7k views
0 votes
Pls

F(x) = 4x^4 +5x -3
G(x)= 4x3 - 3x3 +5.
Find (f-g) (x)

Pls F(x) = 4x^4 +5x -3 G(x)= 4x3 - 3x3 +5. Find (f-g) (x)-example-1
User Anna Lam
by
5.8k points

1 Answer

2 votes

Answer:

After solving we get
\mathbf{(f-g)(x)=-4x^3+7x^2+5x-8}

Option A is correct option.

Explanation:

We are given :


f(x) = 4x^2 +5x -3\\g(x)= 4x^3 - 3x^2 +5

We need to find (f-g)(x)

(f-g)(x) is equal to f(x)-g(x)

So, finding (f-g)(x)


(f-g)(x)=f(x)-g(x)\\(f-g)(x)=4x^2+5x-3-(4x^3-3x^2+5)\\(f-g)(x)=4x^2+5x-3-4x^3+3x^2-5\\Combining \ like \ terms:\\(f-g)(x)=-4x^3+3x^2+4x^2+5x-3-5\\(f-g)(x)=-4x^3+7x^2+5x-8

So, after solving we get
\mathbf{(f-g)(x)=-4x^3+7x^2+5x-8}

Option A is correct option.

User Simon Angatia
by
5.7k points